Exploring the conceptualisation, practices and experiences of talent management: a case of the mining qualification authority - Ramcwana, Christopher Tebogo (University of the Witwatersrand, Johannesburg, 2024)
This research explores the role of talent management with a specific focus on its implementation, processes, and practices. The primary objective of this research is to explore the current conceptualisation of talent management within the Mining Qualifications Authority and to delve into the practices associated with the identification and development of internal talent. This study adopts a qualitative research approach to examine key issues in workplace talent management employing a case study method. Utilising qualitative techniques, including in-depth interviews, the study captures the experiences and practices related to talent management. The research utilised strategic tools, specifically the Talent Management Pipeline Framework and Caruso's nine-grid box, to understand effective talent development and succession planning. The findings illuminate critical challenges within the realm of talent management, including issues of misalignment with organisational goals and deficiencies in evaluation systems. Notably, the study highlights the increasing reliance on informal development methods, emphasizing the role of organisational context in comprehending the intricacies of talent dynamics. Despite positive progress, a critical gap exists in the Mining Qualifications Authority's talent management practices. Cascio and Aguinis' three-fold approach is advocated for aligning employee identification with broader organisational goals. This study highlights the limitations of relying solely on education in talent management, emphasizing that a proficient employee exceeds mere educational qualifications. The research proposes a paradigm shift in talent management strategies, advocating for a broader scope that includes learning, knowledge, talent, skill development, and dynamic skill sets beyond traditional educational boundaries. Embracing this holistic approach positions organisations for success in cultivating a workforce adaptable to the evolving demands of contemporary workplaces
A research report Submitted in fulfillment of the requirements for a Master of Education, In the Faculty of Humanities , Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Talent management; Sector Education and Training Authority; Mining Qualification Authority; SDG-4: Quality education